Are All Anti-Angiogenic Drugs the Same in the Treatment of Second-Line Metastatic Colorectal Cancer? Expert Opinion on Clinical Practice - Lai, Eleonora; Cascinu, Stefano; Scartozzi, Mario (Frontiers in Oncology, 2021)
Targeting tumor-driven angiogenesis is an effective strategy in the management of metastatic colorectal cancer (mCRC); however, the choice of second-line therapy is complicated by the availability of several drugs, the occurrence of resistance and the lack of validated prognostic and predictive biomarkers. This review examines the use of angiogenesis-targeted therapies for the second-line management of mCRC patients. Mechanisms of resistance and anti-placental growth factor agents are discussed, and the role of aflibercept, a recombinant fusion protein consisting of portions of human vascular endothelial growth factor receptor (VEGFR)-1 and VEGFR-2, is highlighted. The novel mechanism of action of aflibercept makes it a useful second-line agent in mCRC patients progressing after oxaliplatin-based chemotherapy, as well as in those with resistance after bevacizumab.